Pharmacological Treatment Pattern and Comorbidities in Parkinson’s Disease Outpatients at Dr. Hasan Sadikin General Hospital Bandung in 2013–2018 - Elke Feliciana; Paulus Anam Ong; Sobaryati Sobaryati (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Parkinson’s disease (PD) is one of many neurodegenerative diseases with symptomatic management, and with the correct pattern of pharmacological treatment PD may have an improved quality of life for a minimum of three years. This study aimed to illustrate treatment patterns and comorbidities in PD patients at Dr. Hasan Sadikin General Hospital, Bandung.Methods: This study was a cross-sectional descriptive study by using total medical records of the period of 2013 to 2018. PD patients receiving pharmacological treatments such as levodopa, anticholinergics, dopamine agonists, or combined therapy were included. Patients with incomplete data and with the previous history of other neurological diseases before PD were excluded from this study.Results: In total, there were 57 patients with PD, of whom most of them were males (79%). Age-wise, PD was most common in 60 to 69-year-olds (32%). The most commonly used treatment pattern was the administration of levodopa (33%). Patients aged younger than 30 years were administered anticholinergics, whereas the older patients (>60 years old) mostly were given levodopa. Comorbidities after PD diagnosis were mostly stroke, dementia, and epilepsy.Conclusions: Males are most affected by PD, and the most commonly used treatment pattern is levodopa monotherapy. PD is most commonly found in patients aged 60 to 69 years. Patients aged below 30 years are administered anticholinergics. The most common comorbidities found are a stroke, followed by dementia and epilepsy. By recognizing the patterns and comorbidities of this disease, the study may provide some insights into choosing the most effective pharmacological therapy for PD.